2016
DOI: 10.1371/journal.pgen.1005981
|View full text |Cite
|
Sign up to set email alerts
|

A Hox Transcription Factor Collective Binds a Highly Conserved Distal-less cis-Regulatory Module to Generate Robust Transcriptional Outcomes

Abstract: cis-regulatory modules (CRMs) generate precise expression patterns by integrating numerous transcription factors (TFs). Surprisingly, CRMs that control essential gene patterns can differ greatly in conservation, suggesting distinct constraints on TF binding sites. Here, we show that a highly conserved Distal-less regulatory element (DCRE) that controls gene expression in leg precursor cells recruits multiple Hox, Extradenticle (Exd) and Homothorax (Hth) complexes to mediate dual outputs: thoracic activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 71 publications
(97 reference statements)
5
70
0
Order By: Relevance
“…As described above, the Hox/HMP site only contributes to abdominal repression and not to thoracic activation [70]. This finding is consistent with previous studies that suggest that only posterior Hox factors mediate strong interactions with HMP proteins on Hox/HMP sites [26,44,45].…”
Section: Case Study: the Distal-less Conserved Regulatory Elementsupporting
confidence: 91%
See 1 more Smart Citation
“…As described above, the Hox/HMP site only contributes to abdominal repression and not to thoracic activation [70]. This finding is consistent with previous studies that suggest that only posterior Hox factors mediate strong interactions with HMP proteins on Hox/HMP sites [26,44,45].…”
Section: Case Study: the Distal-less Conserved Regulatory Elementsupporting
confidence: 91%
“…In the thorax, Antp cooperates with Exd/Hth to stimulate enhancer activity via binding the two Hox/PBC sites of the DCRE [70]. However, the Hox/HMP sites are not required for this activity, indicating that Antp may only specifically work on Hox/PBC sites and not Hox/HMP sites.…”
Section: Case Study: the Distal-less Conserved Regulatory Elementmentioning
confidence: 99%
“…Cloning was facilitated by including flanking EcoR1 and BglII sequences. Annealed oligonucleotides or double stranded DNA fragments were cloned into either placZ-attB or 3xGBE-placZ-attB (Uhl, et al, 2016) and sequence confirmed. To concatenate 6xSPS into larger arrays, a shuttle vector was used to generate a BamH1-6xSPS-BglII-Not1 fragment for reiterative cloning into vectors digested with BglII/NotI (BglII/NotI permits cloning a BamH1/NotI fragment, which can be repeated as desired).…”
Section: Methodsmentioning
confidence: 99%
“…Purified proteins were confirmed by SDS-PAGE with Coomassie blue staining and concentrations were measured by absorbance at UV280 with calculated extinction coefficients. Electromobility shift assays (EMSAs) were performed as previously described using native polyacrylamide gel electrophoresis (Uhl, et al, 2016;Uhl, et al, 2010). Fluorescent labeled probes (3.4nM) were mixed with 22 increasing concentrations of purified CSL (RBPJ) protein in 2-fold steps (from 9.4 to 300nM) with or without purified NICD and Mastermind (Mam) proteins at 550nM.…”
Section: Protein Purification and Electrophoretic Mobility Shift Assamentioning
confidence: 99%
“…The activation of rho, which encodes a serine protease that triggers the release of an EGF ligand, results in the induction of neighboring cells to form an essential set of hepatocyte-like cells known as oenocytes [29][30][31][32]. In contrast, the Distal-less Conserved Regulatory Element (DCRE) contains three Hox/co-factor binding sites that recruit Abd-A/Exd/Hth complexes to repress Distal-less (Dll) gene expression in the abdominal ectoderm [33][34][35]. Dll, which is an appendage selector gene that promotes leg formation in thoracic segments, is thereby restricted from the abdomen to block appendage formation in these segments [36].…”
Section: Introductionmentioning
confidence: 99%